Number of ovarioles in workers descendent from crossings between Africanized and Italian honeybees, Apis mellifera L.: comparison among backcrosses and ancestors colonies - Thuller, Regina H.C. [UNESP]; Malaspina, Osmar [UNESP]; Bueno, Odair C. [UNESP]; Chaud-Netto, José [UNESP] (Sociedade Entomológica do Brasil, 1998)
Comparou-se o número de ovaríolos de operárias de abelhas Apis mellifera L. de 36 colônias de retrocruzamentos (Africanizadas e Italianas) e operárias de colônias ancestrais parentais, endocruzadas e híbridas (F1). Não houve diferença no número de ovaríolos dos ovários direito e esquerdo das operárias. As abelhas híbridas da geração F1 apresentaram de 2 a 31 ovaríolos. O número de ovaríolos nas operárias dos retrocruzamentos africanizados variou de 2 a 56 e nos retrocruzamentos italianos de 2 a 117. A grande variação no número de ovaríolos das abelhas dos retrocruzamentos deveu-se a variabilidade observada na geração parental (abelhas africanizadas: 2 - 16; italianas: 6 - 26) e no F1 (2 - 31).

A comparative study of ovarioles number in workers of bees, Apis mellifera L. of 36 backcrosses colonies (Africanized and Italian), and stock, inbred and F1 colonies was carried out. No difference on the number of ovarioles in right and left ovaries of workers from the colonies used was detected. The hybrid bees from F1 generation presented from 2 to 31 ovarioles. The number of ovarioles observed in backcrossed Africanized workers varied from 2 to 56 and from 2 to 117 in the Italian ones. The range observed in these bees may be partially explained by the variability registered in stock colonies (Africanized workers: 2 - 16; Italian workers: 6 - 26) and in F1 colonies (2 - 31).
Número de ovaríolos em descendentes de cruzamentos entre abelhas africanizadas e italianas, Apis mellifera L.: comparação entre os retrocruzamentos e as colônias ancestrais
Keywords: Insecta; Hymenoptera; Apidae; ovário; abelhas híbridas; Insecta; Hymenoptera; Apidae; ovary; hybrid bees